2022
DOI: 10.3389/fgene.2022.1059640
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of novel elastin gene mutations in eleven families with supravalvular aortic stenosis

Abstract: Background: Supravalvular aortic stenosis (SVAS) is a rare congenital heart disease affecting approximately 1 in 25,000 live births. In some patients it is accompanied by pulmonary artery stenosis, particularly of pulmonary artery branches. Chronic stenosis can lead to cardiac hypertrophy and even circulatory failure. Familial autosomal dominant SVAS is frequently associated with elastin (ELN) gene mutations, whereas Williams-Beuren syndrome is a complex developmental disorder caused by heterozygous microdelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…As mutações que implicam na dosagem da elastina são responsáveis pela EAS. Mais especificamente, 43 mutações já listadas, abrangendo substituições em regiões regulatórias, rearranjos, splicing, além de inserção e deleção de nucleotídeos, são responsáveis pela alteração na dosagem da 20 proteína que ocasiona a EAS (ZHOU et al, 2022).…”
Section: Resultsunclassified
“…As mutações que implicam na dosagem da elastina são responsáveis pela EAS. Mais especificamente, 43 mutações já listadas, abrangendo substituições em regiões regulatórias, rearranjos, splicing, além de inserção e deleção de nucleotídeos, são responsáveis pela alteração na dosagem da 20 proteína que ocasiona a EAS (ZHOU et al, 2022).…”
Section: Resultsunclassified
“…Meanwhile, a genome-wide DNA methylation analysis found that changes in the methylation patterns at the CpG sites of APOA5 (apolipoprotein A5) and PCSK9 (proprotein convertase subtilisin/ kexin type 9) are also associated with valvular aortic stenosis. Conversely, supravalvular aortic stenosis is characterized as an autosomal dominant disease with loss-of-function intragenic mutations or deletions in the ELN (elastin) gene, which result in premature stop codons and/or splicing inefficiency [109][110][111][112][113][114][115]. Williams syndrome (or Williams-Beuren syndrome), a complex of conditions that is comprised of supravalvular aortic stenosis and multiple other diseases, is associated with an approximately 1.5 Mb deletion, which includes the 7q11.23 deletion of ELN and contiguous genes in a region of the genome referred to as the WBSCR (Williams-Beuren syndrome critical region) [109][110][111][112][113][114][115].…”
Section: Genetics Vs Environment Mode Of Inheritance and Variant Disc...mentioning
confidence: 99%
“…Conversely, supravalvular aortic stenosis is characterized as an autosomal dominant disease with loss-of-function intragenic mutations or deletions in the ELN (elastin) gene, which result in premature stop codons and/or splicing inefficiency [109][110][111][112][113][114][115]. Williams syndrome (or Williams-Beuren syndrome), a complex of conditions that is comprised of supravalvular aortic stenosis and multiple other diseases, is associated with an approximately 1.5 Mb deletion, which includes the 7q11.23 deletion of ELN and contiguous genes in a region of the genome referred to as the WBSCR (Williams-Beuren syndrome critical region) [109][110][111][112][113][114][115]. While the aforementioned data serve as a partial blueprint for future SAS-focused genomic explorations, the absence of a definitive genetic etiology of SAS in humans only serves to further highlight the importance of determining the definitive genetic etiology in the canine model of SAS.…”
Section: Genetics Vs Environment Mode Of Inheritance and Variant Disc...mentioning
confidence: 99%
“…Patients with mutations restricted to the ELN gene can show similar cardiovascular abnormalities, but without the distinctive facial features observed in Williams syndrome (Tassabehji et al, 1999; Urbán et al, 2000; Terashita et al, 2019; Zhou et al, 2022), suggesting that ELN hemizygosity is the most important determinant for vascular abnormalities in Williams syndrome. ELN encodes tropoelastin that is mainly produced by vascular smooth muscle cells (Belknap et al, 1996).…”
Section: Introductionmentioning
confidence: 99%